Antecedents to Academic Performance of College Students: An Empirical Investigation. Issue 2 (December 2015) - Duggal, Minakshi; Mehta, Pooja
Academic performance of students is affected by a number of factors. The aim of this study is to investigate the antecedents to the academic performance of college students. The data analysis was done with SPSS factor analysis and chi-square test of Independence. The study reveals that there are a number of factors that influence the academic performance of students and contributes towards the same in different ways. Educational institutions can use the results for policy formulation, parents can use them as a guide for their children and students can come across some factors about which they themselves are not be aware of (hidden factors). Investigations have been carried out on the influence of factors such as gender or parent's education. Beside these, there are also some additional factors that affect the students, but little effort has been made till date. This gap in research has motivated the need to conduct the present study.